PENGARUH MANAGERIAL AGENCY COST TERHADAP FINANCIAL DISTRESS DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL PEMODERASI - Bela Indah Prastiwi; Rosiyana Dewi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The objective of this empirical study is to analyze the effect of Managerial agency cost and Ownership Structure, either separately or simultaneously, on Financial distress in Manufactur Companies that listed on BEI at 2015-2017 . Range of period used in this study is three years, for 2015-2017.Population of the study is all manufacturing companies listed in BEI without delisting, relisting, or moving sector on 2015-2017 period. Method of sampling in this research is purposive sampling method. As the criteria established, there are 261 companies used as sampel. Type of data is secondary data secondary data which is retrieved from financial report manufacturing. In this research, multiple linear regression model is used to analyze data. Result shows that: partially (1) Managerial agency cost has an effect on Financial distress, and (2) Ownership Structure has an effect on Financial distress. Simultaneously Managerial agency cost and Ownership Structure has effect on Financial distress.